Why have tobacco control policies stalled? Using genetic moderation to examine policy impacts. - Jason M Fletcher (PLoS ONE)
Background Research has shown that tobacco control policies have helped produce the dramatic decline in use over the decades following the 1964 surgeon general's report. However, prevalence rates have stagnated during the past two decades in the US, even with large tobacco taxes and expansions of clean air laws. The observed differences in tobacco control policy effectiveness and why policies do not help all smokers are largely unexplained. Objective The aim of this study was to determine the importance of genetics in explaining response to tobacco taxation policy by testing the potential of gene-policy interaction in determining adult tobacco use. Methods A moderated regression analysis framework was used to test interactive effects between genotype and tobacco policy in predicting tobacco use. Cross sectional data of US adults from the National Health and Nutrition Examination Survey (NHANES) linked with genotype and geocodes were used to identify tobacco use phenotypes, state-level taxation rates, and variation in the nicotinic acetylcholine receptor (CHRNA6) genotype. Tobacco use phenotypes included current use, number of cigarettes smoked per day, and blood serum cotinine measurements. Results Variation in the nicotinic acetylcholine receptor was found to moderate the influence of tobacco taxation on multiple measures of tobacco use. Individuals with the protective G/G polymorphism (51% of the sample) responded to taxation while others had no response. The estimated differences in response by genotype were C/C genotype: b = -0.016 se = 0.018; G/C genotype: b = 0.014 se = 0.017; G/G genotype: b = -0.071 se 0.029. Conclusions This study provides novel evidence of "gene-policy" interaction and suggests a genetic mechanism for the large differences in response to tobacco policies. The inability for these policies to reduce use for individuals with specific genotypes suggests alternative methods may be needed to further reduce use.